A comparative Survey on the Effect of Enamel Matrix Protein in Treatment of Two Wall Intrabony Periodontal Defects (Alone or in Combination with Autogenous Bone Graft) - A.Eskandari; N.Abolfazli (Tehran University of Medical Sciences, 2005)
Statement of Problem: Regenerative periodontal procedures are one mode of therapy that attempts to restore the lost supporting structures of the dentition around a previously diseased root surface.Purpose: The purpose of this study was comparison between Enamel matrix proteins (EMP) used alone or in combination with autogenous bone graft (ABG) in the treatment of human intrabony periodontal defects.Materials and Methods: This clinical trial study, was done on 8 pairs of matched two wall intrabony periodontal defects with 5 mm or more probing depth and 3 mm or more depth of intrabony componentfollowing phase I therapy. In control sites Enamel matrix proteins (EMP) and in lest sites EMP with autogenous bone graft (ABG) was used.Results: No differences were found in terms of oral hygiene and defect characteristics, at baseline. Six months after treatment, both procedures significantly improved the clinical probing depth and clinical attachment level. Although bone fill was significant for both groups but EMP+ABG significantly showed more bone fill and defect resolution (bone fill 2.75mm versus 3.67mm). Crestal resorption was the same for both groups and its difference was not significant.Conclusion: The results of this study demonstrates that both procedures improves clinical parameters and combined use of EMP with autogenous bone graft will promote more bone fill and more defect resolution. A difficulty in obtaining sufficient amounts of autogenous bone from intra oral sites is one of the limitations ofthis procedure.